2018
DOI: 10.3390/ijms19103110
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 in Liver Injury, Metabolic and Immune Regulation

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is a transmembrane glycoprotein that is expressed on epithelial, endothelial and immune cells. CEACAM1 is a differentiation antigen involved in the maintenance of epithelial polarity that is induced during hepatocyte differentiation and liver regeneration. CEACAM1 regulates insulin sensitivity by promoting hepatic insulin clearance, and controls liver tolerance and mucosal immunity. Obese insulin-resistant humans with non-alcoholic fatty liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 231 publications
0
46
0
Order By: Relevance
“…Indeed, liver flush from cold-stored WT livers was found to increase mRNA levels coding for MCP1, CXCL2 and CXCL10, whereas liver flush from CC1-ly identified as a substrate of the insulin receptor tyrosine kinase in rat hepatocytes (12,13), and abundantly expressed by the bile capillary side of hepatocytes in rodents and humans, CEACAM1 is involved in hepatocyte differentiation/liver regeneration, and increasingly recognized as the master regulator of insulin clearance, while preventing metabolic disorders, such as diabetes and nonalcoholic steatohepatitis (NASH) (14,15). The emerging evidence of hepatic CEACAM1 residing at the central hub of immune liver injury and metabolic homeostasis (16) provides the rationale to study its relevance in IRI-OLT in the current study.…”
Section: Hepatic Ceacam1 Expression Indicates Donor Liver Quality Andmentioning
confidence: 99%
“…Indeed, liver flush from cold-stored WT livers was found to increase mRNA levels coding for MCP1, CXCL2 and CXCL10, whereas liver flush from CC1-ly identified as a substrate of the insulin receptor tyrosine kinase in rat hepatocytes (12,13), and abundantly expressed by the bile capillary side of hepatocytes in rodents and humans, CEACAM1 is involved in hepatocyte differentiation/liver regeneration, and increasingly recognized as the master regulator of insulin clearance, while preventing metabolic disorders, such as diabetes and nonalcoholic steatohepatitis (NASH) (14,15). The emerging evidence of hepatic CEACAM1 residing at the central hub of immune liver injury and metabolic homeostasis (16) provides the rationale to study its relevance in IRI-OLT in the current study.…”
Section: Hepatic Ceacam1 Expression Indicates Donor Liver Quality Andmentioning
confidence: 99%
“…Among 11 known CEACAM1 isoforms [66], only isoform-1 possesses the ability to interact with FASN through the insulin-dependent mechanism and exactly that isoform was detected in the samples of studied groups [50,53]. Turning to the obtained results of quantitative measurements, we assumed that the suppression of CEACAM1 has appeared as a consequence of GDM and T2DM manifestation ( Table 3 and Figure 4).…”
Section: Discussionmentioning
confidence: 91%
“…In the past years, it had been studied as a tumor marker of different types of cancer. On the other hand, earlier studies indicated that CEACAM1 was also related to some metabolic diseases [17][18][19]. Previous articles reported that the hepatic CEACAM1 expression was markedly decreased in the severely obese subjects, high grade fatty livers and NASH, but not different between diabetic and non-diabetic persons [20].…”
Section: Discussionmentioning
confidence: 97%